Influence of Social Support on Treatment Adherence and Self-care among Type 2 diabetes mellitus patients in Field Practice Areas of a Tertiary Medical College in Bangalore- A Cross-sectional Study - G Hegde, Vinaykumar; S, Saraswathi; Mukhopadhyay, Amita; Debata, Ipsita; Sagar Panda, Prem; R Bhagavati, Vilas (Indian Journal of Community Health, 2025)
Background: As a chronic illness, type 2 diabetes necessitates regular self-care. In this context, the social assistance provided is crucial. Aim and Objective: To evaluate the levels of social support in type 2 Diabetes Mellitus (T2DM) patients and to identify the influence of social support on treatment adherence and self-care activities. Methodology: A cross-sectional study was conducted among 400 T2DM patients in the medical college's field practice areas. Data regarding the sociodemographic details, clinical and treatment history, social support level (Social Support Rating Scale), and management of self-care activities (Summary of Diabetes Self-care activities) were collected. Compiled data was analyzed using IBM SPSS software. Data was interpreted as frequencies, percentages, and means. Association was tested using the Chi-square test and Spearman’s correlation. A p-value less than 0.05 was deemed significant. Results: There were 53% females and 47% males. Most participants (83.25%) had a moderate level of social support. Medication adherence and blood glucose monitoring were the most practiced self-care practices. Support level was significantly associated with activities of self-care (proper dietary practice, regular physical activity, and foot hygiene). Conclusion: More than two-thirds of the patients had a moderate to high social support level, which significantly correlated with self-care activities.